KAJIAN LITERATUR MODEL KONSEPTUAL KEBERHASILAN E-GOVERNMENT - Bernadus Gunawan Sudarsono; Sri Poedji Lestari (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
The use of internet technology in the government environment is known as electronic government or e-government. In simple terms, e-government or digital government is an activity carried out by the government by using information technology support in providing services to the community. In line with the spirit of bureaucratic reform in Indonesia, e-government has a role in improving the quality of public services and helping the process of delivering information more effectively to the public. Over time, the application of e-Government has turned out to have mixed results. In developed countries, the application of e-Government systems in the scope of government has produced various benefits ranging from the efficiency of administrative processes and various innovations in the field of public services. But on the contrary in the case of developing countries including Indonesia, the results are more alarming where many government institutions face obstacles and even fail to achieve significant improvements in the quality of public services despite having adequate information and communication technology. The paradigm of bureaucrats who wrongly considers that the success of e-Government is mainly determined by technology. Even though there are many factors outside of technology that are more dominant as causes of failure such as organizational management, ethics and work culture. This study aims to develop a model of success in the application of e-Government from several best practice models in the field of information technology that have been widely used so far using literature studies as research methods. The results of the study show that the conceptual model of the success of the implementation of e-Government developed consists of 17 determinants of success..Keywords: Model, Factor, Success, System, e-Government